A functional approach to translation quality assessment: Categorizing sources of translational distortion in medical abstracts - Martikainen, Hanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
The translation of Cochrane Systematic Review abstracts plays an important role in ensuring the communication of medical research results to the non-English-speaking public. The presentation of results should, of course, be free of errors and as objective as possible. Translation, however, is a highly subjective activity requiring extensive interpretation and is prone to errors. Translated Cochrane abstracts therefore contain elements that could affect readers’ interpretation of the results of a Review, and that specifically could have an impact on the effectiveness of the intervention studied. Guided by the function of these translated texts, we have categorized such sources of distortion into a context-specific typology that will be used to measure translational distortion in Cochrane abstracts. Building on previous research and empirical corpus analysis, the typology accounts not only for translation errors with considerable potential impact, but also for biased translations of phraseological and modal structures that can markedly affect readers’ interpretation of the degree of certainty expressed by authors.